(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2019)
The article presents two gestures corresponding to two profound new understandings of Peirce’s Continuum (Vargas 2015) and Peirce’s Existential Graphs (Oostra 2010). Vargas and Oostra have revolutionized Peirce’s mathematical studies, thanks to a first complete model for Peirce’s continuum provided by Vargas, and thanks to the emergence of intuitionistic existential graphs provided by Oostra. The article aims at showing how these careful mathematical constructions can be encrypted in very simple gestures.